Escherichia coli CrfC Protein, a Nucleoid Partition Factor, Localizes to Nucleoid Poles via the Activities of Specific Nucleoid-Associated Proteins - Taniguchi, Saki; Kasho, Kazutoshi; Ozaki, Shogo; Katayama, Tsutomu (Frontiers in Microbiology, 2019)
The Escherichia coli CrfC protein is an important regulator of nucleoid positioning and equipartition. Previously we revealed that CrfC homo-oligomers bind the clamp, a DNA-binding subunit of the DNA polymerase III holoenzyme, promoting colocalization of the sister replication forks, which ensures the nucleoid equipartition. In addition, CrfC localizes at the cell pole-proximal loci via an unknown mechanism. Here, we demonstrate that CrfC localizes to the distinct subnucleoid structures termed nucleoid poles (the cell pole-proximal nucleoid-edges) even in elongated cells as well as in wild-type cells. Systematic analysis of the nucleoid-associated proteins (NAPs) and related proteins revealed that HU, the most abundant NAP, and SlmA, the nucleoid occlusion factor regulating the localization of cell division apparatus, promote the specific localization of CrfC foci. When the replication initiator DnaA was inactivated, SlmA and HU were required for formation of CrfC foci. In contrast, when the replication initiation was inhibited with a specific mutant of the helicase-loader DnaC, CrfC foci were sustained independently of SlmA and HU. H-NS, which forms clusters on AT-rich DNA regions, promotes formation of CrfC foci as well as transcriptional regulation of crfC. In addition, SeqA, a hemimethylated nascent DNA region-binding protein stimulated formation of CrfC foci. However, IHF, a structural homolog of HU, MatP, the replication terminus-binding protein, Dps, a stress-response factor, MukB, the chromosomal structure maintenance protein, and FtsZ, an SlmA-interacting factor in cell division apparatus, little or only slightly affected CrfC foci formation and localization. Taken together, these findings suggest a novel and unique mechanism that CrfC localizes to the nucleoid poles in two steps, assembly and recruitment, dependent upon HU, MukB, SeqA and SlmA, which is stimulated directly or indirectly by H-NS and DnaA. These factors might concordantly affect specific nucleoid substructures. Also, these nucleoid dynamics might be significant in the role for CrfC in chromosome partition.